2
$\begingroup$

Consider the following ODE:

\begin{equation} (\cos x)y''-2(\sin x)y'-(\cos x)y=e^x \end{equation}

The above equation is a second order linear ODE. However, I noticed that it doesn't have constant coefficients, so I cannot "guess" the solution is of the form $e^{\lambda x}$. Im very confused by this, since I have never solved a 2nd order ODE with variable coefficients. The first part of the question says:

(a)

Show that the ODE is of the form:

\begin{equation} \frac{d^2}{dx^2}(f(x)y)=e^x \end{equation}

by finding the function f.

(b)

Hence, find the general soluion of he differential equation.

For part (a) I have have no idea where to begin, but I tink that If i knew how to complete part (a) I would be able to find the general solution since I hae done things like that many times. Any help (part a especially) would be much appreciated. Thanks in advance.

$\endgroup$
1
$\begingroup$

a) you have to find $f(x)$ such that $\frac{d^2}{dx^2}(f(x)y)=e^x$, but $$e^x=\frac{d^2}{dx^2}(f(x)y)=\frac{d}{dx}(f'(x)y+f(x)y')=f''(x)y+f'(x)y'+f'(x)y'+f(x)y''$$ So from the equation $$(\cos x)y''-2(\sin x)y'-(\cos x)y=e^x=f''(x)y+2f'(x)y'+f(x)y''$$ we obtain that $f(x)=\cos x$.

b) you can before find the soluction for the associate homogeneous equaction: $$(\cos x)y''-2(\sin x)y'-(\cos x)y=0$$ Using what we have seen in the point a) we have $$0=\frac{d^2}{dx^2}(\cos (x)\cdot y)$$ so $\cos (x) \cdot y$ or it's a costant or a polinomial with $deg=1$. So a base of the associate homogeneous equaction it's $c_1\cdot sec(x)+c_2\cdot xsec(x)$ ($sec(x)=\frac{1}{\cos x}$). Now from $$e^x=\frac{d^2}{dx^2}(f(x)y)$$ we can easily obtain a particular soluction like $sec(x)e^x$. Summing the particular solution with the general soluction of the associate homogeneous equaction you find what you want.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

The differential equation is $y''-2(\tan x )y'-y=e^x\sec x$.Calculate the invariant $I=Q-(1/4)P^2-(1/2)dP/dx$ where $P,Q,R$ have usual meaning and $I=0$ by calculation.So the substitution $y=ve^{-1/2\int Pdx}=v\sec x$ transforms the differential equation into $v''+Iv=Re^{1/2\int P dx}$,i.e. $v''=e^x$,integrating $v=e^x+Ax+B$ and $y=v\sec x$,which is the solution of the second order linear differential equation and here $f(x)=\cos x $ as per your question as $y=v\sec x$ implies $y\cos x=v$ so that $D^2(y\cos x)=e^x$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.